Evolution de la gestion de l’information a l’intelligence économique Etude de cas : la mise en place d’un système de veille stratégique a la NAFTAL - Dahmane Bounoua Senouci (My University, 2018)
In a context of change in the economic environment organizations, by always advance more innovative in the areas of technology and communication, but also the competitiveness of increasingly aggressive competition information management it has quickly change very profoundly in how to run what is commonly called the economic intelligence, it is everywhere, on all the documentation, book and thesis research and despite that many organizations can’t explain just yet and clearly, what business intelligence The objective that this research aims to trace and explain the evolution of the management of traditional business intelligence has information which will promote a better understanding of its components and its implementation
Keywords: information management, business intelligence, business intelligence, knowledge management